Reshaping Society through Analytics, Collaboration, and Decision Support : Role of Business Intelligence and Social Media - Iyer, Lakshmi S.; Power, Daniel J. (Annals of Information Systems,, 2015)
Chapter 1: Introduction        Lakshmi Iyer and Daniel J. Power Chapter 2: Big Data panel at SIGDSS Pre-ICIS Conference 2013 A Swiss-Army Knife? The Profile of a Data Scientist        Barbara Dinter and David Douglas Chapter 3: Creating a Data-Driven Global Society        Daniel J. Power Chapter 4: Agile Supply Chain Decision Support System        Jaehun Lee, Hyunbo Cho, and Yong Seog Kim Chapter 5: Hawkes Point Processes for Social Media Analytics        Amir Hassan Zadeh and Ramesh Sharda Chapter 6: Using Academic Analytics To Predict Dropout Risk In E-learning Courses        Rajeev Bukralia, Amit V. Deokar, and Surendra Sarnikar Chapter 7: Membership Reconfiguration in Knowledge Sharing Network: A Simulation Study        Suchul Lee, Yong Seog Kim, and Euiho Suh Chapter 8: On the Role of Ontologies in Information Extraction        Sagnika Sen, Jie Tao, and Amit V. Deokar Chapter 9: A Quantitative Approach to Identify Synergistic IT Portfolios        Ken Pinaire and Surendra Sarnikar Chapter 10: Introduction to Research in Progress        Thilini Ariyachandra and Amit Deokar Chapter 11: Towards Attentive In-Store Recommender Systems: Detecting Exploratory vs. Goal-oriented Decisions        Jella Pfeiffer, Thies Pfeiffer, and Martin Meißner Chapter 12: Engaging with Online Crowd: A Flow Theory Approach        Cuong Nguyen, Onook Oh, Abdulrahman Alothaim, Triparna de Vreede, and Gert Jan de Vreede Chapter 13: Modeling Dynamic Organizational Network Structure        Seokwoo Song and Seong-Hoon Choi Chapter 14: Teaching Analytics, Decision Support, and Business Intelligence: Challenges and Trends        Babita Gupta and Uzma Raja Chapter 15: Data Analysis of Retailer Orders to Improve Order Distribution        Michelle LF Cheong and Murphy Choy Chapter 16: An Online Graduate Certificate Credential Program at the University of Arkansas        Timothy Paul Cronan, David E. Douglas and Jeff Mullins Chapter 17: Business Intelligence at Bharti Airtel Ltd        Prabin Kumar Panigrahi.